Nursing Students' Narrative Text Writing Improvement with Animation Video - VALEN, Yuniarti Rherhe; DE VEGA, Nofvia (Research and Innovation in Applied Linguistics, 2023)
The purpose of this study was to determine if the animation video can enhance students' narrative writing skills at Universitas Borneo Tarakan. This research employed Classroom Action Research as its methodology (CAR). In this study, there were 21 of the sample. An observation checklist, an interview, and a writing test were used in this study. In this study, there were two success criteria. First, students should get at least a 75.0 on their writing assignments. Second, class participation and instructor engagement must both total 80. In this study, the researcher did the analysis of the data using a combination of different methods. Quantitative data analysis was used to evaluate the results of the written tests, while qualitative data analysis was used to evaluate the results of the observation checklist and interviews. This study found that the use of animated videos led to a rise in students' writing scores between the first and second cycles of instruction. Attendance at the first meeting was 33%, and at the second it was at 57%. The attendance rates for the first and second meetings of the second cycle were 52% and 76%, respectively. The outcome of the observation checklist demonstrates the improvement, which can also be seen for itself. Based on the checklist of observable behaviors, it was clear that the training had been effective. From what we can gather from the interviews, using animation videos in the classroom is beneficial and makes both teachers and students happy. The results of this study suggest that having students practice their writing skills with the aid of animated videos can help them achieve better results.